Pengaruh Investasi Swasta, Kepemilikan Perangkat Seluler, dan Pengeluaran Per Kapita terhadap PDRB ADHK Indonesia 2019-2024 - Rifandi Rifandi (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of private investment, mobile phone ownership, and per capita expenditure on Gross Regional Domestic Product at Constant Prices (GRDP) in 34 provinces of Indonesia during the period 2019-2024. The transformation of Indonesia's economy in the digital era has created complex dynamics where traditional factors such as investment and consumption interact with information technology adoption to drive regional economic growth. This research employs a quantitative approach with panel data regression analysis using the Random Effect Model (REM). Data were obtained from the Central Bureau of Statistics (BPS) and the Investment Coordinating Board (BKPM) across 204 observations (34 provinces over 6 years). The results indicate that private investment has a positive and significant effect on GRDP, with a coefficient of 0.289023 and p-value of 0.0306. Per capita expenditure has a positive and significant effect as the most dominant factor with a coefficient of 7.295115 and p-value of 0.0116. However, mobile phone ownership has a negative and significant effect on GRDP with a coefficient of -526.5233 and p-value of 0.0495. The coefficient of determination (Adjusted R²) of 0.5574 indicates that 55.74% of the variation in GRDP can be explained by the three independent variables, while the remaining 44.26% is explained by other variables outside the research model. These findings provide important implications for the government in formulating investment policies, digital literacy improvement, and household consumption stimulus to drive inclusive and sustainable regional economic growth in Indonesia.